Generation of Human-Induced Pluripotent Stem Cells by a Nonintegrating RNA Sendai Virus Vector in Feeder-Free or Xeno-Free Conditions - Chad C. MacArthur; Andrew Fontes; Namritha Ravinder; David Kuninger; Jasmeet Kaur; Matthew Bailey; Antje Taliana; Mohan C. Vemuri; Pauline T. Lieu (Stem Cells International)
The generation of induced pluripotent stem cells (iPSCs) from somatic cells has enabled the possibility of providing unprecedented access to patient-specific iPSC cells for drug screening, disease modeling, and cell therapy applications. However, a major obstacle to the use of iPSC for therapeutic applications is the potential of genomic modifications caused by insertion of viral transgenes in the cellular genome. A second concern is that reprogramming often requires the use of animal feeder layers and reagents that contain animal origin products, which hinder the generation of clinical-grade iPSCs. Here, we report the generation of iPSCs by an RNA Sendai virus vector that does not integrate into the cells genome, providing transgene-free iPSC line. In addition, reprogramming can be performed in feeder-free condition with StemPro hESC SFM medium and in xeno-free (XF) conditions. Generation of an integrant-free iPSCs generated in xeno-free media should facilitate the safe downstream applications of iPSC-based cell therapies.